DETERMINAN FACTORS OF RELATED TO KNOWLEDGE ABOUT VACCINE AND ADVERSE EVENTS POST-COVID-19 IMMUNIZATION IN LOKA VILLAGE - Elly Lilianty Sjattar; Abdul Majid; Indra Gaffar; Silvia Malasari; A. Nur Ilmi Tenri Dio (Universitas Islam Negeri Alauddin Makassar, 2023)
Vaccines are one of the most economical and effective ways to prevent an infectious disease. Vaccination at the village or kelurahan level affects the success of national scale vaccination. The variety of public knowledge about vaccination causes the percentage of vaccinations not to reach the maximum level and misinterpretations about co-occurrence after the covid-19 immunization. Therefore, it is very important to know the determinants of knowledge about vaccines and follow-up events after Covid-19 immunization in Loka Village. This research is a cross sectional study design. The population is the people of Loka Village, with a sample of 400 respondents, to see the correlation of characteristics with knowledge about vaccines and knowledge about follow-up events after Covid-19 immunization using the Spearman Rho correlation test. The results of the study found that there was a correlation between age with knowledge of vaccines r = 0.216, education r = 0.186, and occupations with knowledge of vaccines r = -0.114, and occupations with knowledge of post-immunization follow-up events r = 0.165 positive correlation. Age and education were positively correlated with knowledge about vaccines, while occupation was negatively correlated. However, the work is positively correlated with knowledge about post-immunization